A4_12 Relativity in the Christmas Spirit - Sier, Anya; Coulson, Rebecca; Wayman, James; Shehzad, Habeebah; Nuttall, Heather (Physics Special Topics, 2022)
In this paper the speed at which Santa’s sleigh travels is investigated with a focus on the relativistic effects. It is found that Santa is not travelling at great enough speeds for time dilation and length contraction to have a significant effect and that the red-shift of Santa and his sleigh causes a ∆λ = 9 nm shift. This is not significant enough to change the colour of Santa to an observer. It is also found that in order for Santa to be shifted from green to red, he must travel at 0.271 c.